The principle of moral duty according to Kant - hemiani, sabah (Journal of Social Sciences and Humanities, 2021)
Most if the previous moral schools of thought neglected the element of duty or moral imperative, and morals were merely searching for happy ends. Every ethical theory has linked goodness with pleasure, happiness, or btnrefit, and neglected an important aspect of morality except the obligatory aspect. The reason for this is that Greek philosophers have conceived virtue as a kind of psychological tranquility ,while the moral life an effort, struggle , and obligation .As for the utilitarian . Philosophers if the modern era, they considered goodnes merely a tangible thing, which led them to measure the results of actions with an experimental standard. However, we find that the modern era has witnessed new ethical trends whose owners wanted to make duty a basic cornerstone of mora ls , this is what we find with the Geraman philosopher Immanuel Kant(1724-1804) as one of the representatives of the mental critical trend in the field of ethics . He believes that duty is the only source of moral imperative , so the morality of action is not referred to the sensory experience and is not dependent on some utilitarian Considerations related to the results of action , but is linked to our sense of obligation.The latter represents the total inner moral law to which the humman nature is subject to at every time and place and which is contained in the core of the ethical act itself out of respect for the mind itself thus ; duty is synomous with law and law ‘s accountability is mainly related to the mind taking into consideration that man is a rational being and principles of the mind are absolute.